"Ductile" Fracture of Metallic Glass Nanolaminates. Issue 21 (3rd August 2017) - Fan, Zhe; Li, Jin; Yang, Yingchao; Wang, Jian; Li, Qiang; Xue, Sichuang; Wang, Haiyan; Lou, Jun; Zhang, Xinghang
Abstract: Most metallic glasses are brittle as deformation induces low‐density sporadic shear bands and severe shear localization proceeding catastrophic failure. Here, it is demonstrated that the introduction of crystalline nanolayers with appropriate dimension can substantially suppress shear localization in metallic glasses, as manifested by ubiquitous ductile dimples in amorphous phase. Furthermore, dimple sizes can be tailored by tuning the dimension of layer thickness. Additionally unlike instantaneous crack propagation occurring in most metallic glasses, crack propagation occurs in a highly periodic and "zigzag" fashion, and shows clear size dependence for metallic glass nanolaminates. Thus, it is a promising approach to promote ductility in metallic glasses while maintaining high strength by synthesizing metallic glass nanolaminates with certain layer thickness. Molecular dynamics simulations demonstrate that crystalline/amorphous interfaces can block crack propagation in crystalline layers and delocalize strain in amorphous layers, and suggest that "zigzag" crack propagation could be achieved through dislocation slips in crystalline layers. Abstract : Ductile fracture: This study highlights the significance of layer interface on tailoring plasticity of metallic glass nanolaminated composites. The observations of ductile dimples and zig‐zag ("saw‐tooth") fracture path are surprising and provide direct evidence for "ductile" fracture of metallic glass nanocomposites. Moreover, both dimple sizes and fracture path can be tailored by the layer thickness.